Multistage zircon growth recording polyphase metamorphic evolution caused by pulsed granitoid intrusions into a low‐P/T type metamorphic belt: P–T–D–t evolution of migmatites in the Ryoke belt, southwest Japan. (4th August 2022) - Kawakami, Tetsuo; Ichino, Tomoe; Kazuratachi, Keiichi; Sakata, Shuhei; Takatsuka, Kota
Abstract: We report contrasting pressure–temperature–time ( P–T–t ) paths of migmatites developed in the highest‐grade metamorphic zone (Grt–Crd zone) and the contact metamorphic zone (Crd–Kfs zone) of the Mikawa area, Ryoke belt, southwest Japan to discuss the complex P–T–D–t evolution of the middle crust that experienced pulsed granitoid intrusions. In the Grt–Crd zone, sillimanite‐grade high‐ T metamorphic condition prevailed from ca. 97 to 87 Ma, followed by cooling to ~500 °C, ~4 kbar. The intrusion of gneissose granitoids below the Grt–Crd zone isobarically reheated the Grt–Crd zone rocks again to the sillimanite‐grade high‐ T condition at ca. 84 Ma. This was followed by ca. 71–70 Ma contact metamorphism. Ductile deformation that formed and folded the foliation of migmatites started before ca. 89 Ma and continued at least until ca. 84 Ma in the Grt–Crd zone. On the other hand, ca. 74 Ma age of the Crd–Kfs zone migmatite developed around the Inagawa Granodiorite in addition to ca. 70 Ma age of a syn‐tectonic pegmatite vein revealed that the intrusion of "75–69 Ma granitoids" caused partial melting and locally triggered low‐strain ductile deformation in their contact aureoles. Comparison with other areas of the Ryoke belt suggests that plutono‐metamorphic evolution of the Mikawa and Aoyama areas are similar with each other in that ca. 80 Ma reheating events (i.e., contact metamorphism) are observed, while absence of separate reheating event postdating peak metamorphism in the Yanai area is a rather uncommon feature in the Ryoke belt.